Numerical modelling of non-cavitating and cavitating flow around a marine propeller - Woo, Jason Jia Wen (2017)
The performance of a marine propeller is often studied in two conditions – non cavitating and cavitating flow. In the latter case, cavitation affects performance and causes significant damage to marine propellers. By predicting cavitation, propeller design can be evaluated and optimized for better performance. Although many studies on numerical modelling of propeller flows with and without cavitation have been done to date, some issues such as mesh generation strategies and selection of turbulence model still need to be addressed. This study sought to model non-cavitating and cavitating flow around a marine propeller using an unstructured mesh and the steady RANS solver available in ANSYS Fluent. With regard to non-cavitating flow, the RANS solver coupled with SST k-ω turbulence model was used. In the case of cavitating flow, the homogenous multi-phase mixture RANS solver coupled with SST k-ω turbulence model and Schnerr-Sauer’s cavitation model was used. The results obtained for the case of non-cavitating flow showed thrust and torque coefficient decreasing with increasing advance coefficient, similar to trends seen in typical open water diagrams. As for the case of cavitating flow, cavitation patterns at two operating conditions, illustrated by iso-surfaces of vapour volume fraction, showed an overprediction of suction side sheet cavitation in comparison with experimental results. In addition, K_Tand K_Q found in cavitating flow were smaller when compared to that in non-cavitating flow. While steady state calculations were carried out in this study to reduce computational effort, future studies employing an unsteady solver can be done to capture any unsteady cavitation and its behaviour over time.